Metodología administrativa-financiera para determinar el valor razonable de muebles y enseres del hospital Pablo Arturo Suárez (H.P.A.S.) en la ciudad de Quito, adoptando la norma internacional de contabilidad (NIC 16) y las normas internacionales de información financiera (NIIF´S 1 y 5) - Maldonado Puente, Karla Margoth (2012)
It was considered the Financial Reporting Standards, International Accounting Standards and International Financial Reporting Standards which will help the valuation of assets, preparation, lifting, cleaning of furniture and equipment inventories taking into account the accounting policies adopted by the institution for the presentation of financial statements with VI real and reliable to a certain date which help in correct decision making process.